Riding the Kuroshio Current: Stepping stone dispersal of the Okinawa tree lizard across the East Asian Island Arc. (18th October 2017) - Yang, Shang‐Fang; Komaki, Shohei; Brown, Rafe M.; Lin, Si‐Min
Abstract: Aim: Located hundreds of kilometres offshore of continental mainland Asia, the extremely high level of land vertebrate endemism in the East Asian Island Arc provides an excellent opportunity to test hypotheses regarding biogeographic processes and speciation. In this study, we aim to test alternative explanations for lineage diversification (vicariance versus dispersal models), and further develop a temporal framework for diversification in our focal taxon, which is consistent with the known age of these islands. We achieve these tests by investigating the historical biogeography of the Okinawa tree lizard ( Japalura polygonata ), one of the few widely‐distributed reptiles across this archipelago. Location: The East Asian Island Arc: (1) Central Ryukyu (Amami and Okinawa groups); (2) Southern Ryukyu (Miyako and Yaeyama groups); (3) Taiwan and adjacent islands. Methods: A total of 246 tissues were sampled from 10 localities in the Ryukyu archipelago and 17 localities in Taiwan, covering the entire distributional range of this species, including all subspecies. DNA sequences of the mitochondrial cytochrome b, 16S ribosomal RNA, nuclear BACH‐1 and RAG‐1 genes (total: 4, 684 bp) were obtained from these samples. We used maximum likelihood and Bayesian methods to infer phylogeny and divergence time, and used a model‐fitting method of biogeographical inference to estimate ancestral range evolution. Results: Multiple lines of evidence combine to identify a general pattern of dispersal‐mediated diversification northward through the archipelago, following initial dispersal from Taiwan. These included (1) a phylogenetic estimate, revealing a sequential, south‐to‐north branching pattern; (2) ancestral range estimation, inferring multiple overseas dispersals and subsequent colonization of new landmasses; and (3) a reduction in genetic variation observed in successively‐diverging lineages, decreasing from Taiwan northward, towards more remote islands. These results provide strong statistical support for an interpretation of successive bouts of dispersal via the powerful, well‐documented, south‐to‐north Kuroshio Current. Estimation of divergence times suggests that most clades in southern Ryukyu and Taiwan diverged early, giving rise to lineages that have remained isolated, and that more recently‐diverged lineages then colonized northward to subsequently occupy the landmasses of the Central Ryukyu archipelago. Main conclusions: Our general inference of biogeographic history in Japalura polygonata suggested that this species originated on Taiwan and the Yaeyama group, and arrived at its current distribution in Miyako, Okinawa, Toku and Amami islands by a series of stepping‐stone dispersals, which we report for the first time for a terrestrial vertebrate endemic to this region.